Maternal-Fetal Microchimerism: Impacts on Offspring's Immune Development and Transgenerational Immune Memory Transfer - Malinská, N; Grobárová, V; Knížková, K; Černý, J (Physiological research, 2024)
Maternal-fetal microchimerism is a fascinating phenomenon in which maternal cells migrate to the tissues of the offspring during both pregnancy and breastfeeding. These cells primarily consist of leukocytes and stem cells. Remarkably, these maternal cells possess functional potential in the offspring and play a significant role in shaping their immune system development. T lymphocytes, a cell population mainly found in various tissues of the offspring, have been identified as the major cell type derived from maternal microchimerism. These T lymphocytes not only exert effector functions but also influence the development of the offspring's T lymphocytes in the thymus and the maturation of B lymphocytes in the lymph nodes. Furthermore, the migration of maternal leukocytes also facilitates the transfer of immune memory across generations. Maternal microchimerism has also been observed to address immunodeficiencies in the offspring. This review article focuses on investigating the impact of maternal cells transported within maternal microchimerism on the immune system development of the offspring, as well as elucidating the effector functions of maternal cells that migrate through the placenta and breast milk to reach the offspring.
Keywords: Maternal-Fetal Exchange; Pregnancy; těhotenství; maternofetální výměna látek; ženské pohlaví; imunologická paměť; zvířata; Animals; Chimerism; Humans; lidé; chimérismus; Immunologic Memory; Female